1971
DOI: 10.2170/jjphysiol.21.659
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Potassium Electrolytes and “ Basal ” Skin Potential Levels in Male and Female Subjects

Abstract: Summary When palmar skin potential level (SPL) is recorded duringperiods of minimal arousal sweating, and a concentration of potassium chloride within physiological limits is used for the external electrolyte, the value of the "basal" SPL (BSPL) recorded can be expressed as a function of the external/epidermal potassium concentration gradient.The present study reports comparison of BSPL values obtained with the use of physiologically comparable concentrations of sodium and potassium chlorides. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This skin impedance results from two electrical pathways: one through the extracellular channels in the epidermis and one through the sweat ducts. Christie and Venables (1971) have shown that during resting conditions sweat glands are minimally active. Thus we believe that at rest most of the current flows primarily through the extracellular channels in the epidermis and little through the sweat gland ducts.…”
Section: Variations Of Z With Successive Scotch Tape Strippingmentioning
confidence: 99%
See 1 more Smart Citation
“…This skin impedance results from two electrical pathways: one through the extracellular channels in the epidermis and one through the sweat ducts. Christie and Venables (1971) have shown that during resting conditions sweat glands are minimally active. Thus we believe that at rest most of the current flows primarily through the extracellular channels in the epidermis and little through the sweat gland ducts.…”
Section: Variations Of Z With Successive Scotch Tape Strippingmentioning
confidence: 99%
“…Measured with respect to the body interior the skin potential ranges between 10 mV and −70 mV with an average value of −15 mV on the forearm. Christie and Venables (1971) have related this basal skin potential level (BSPL) to the Nernst equation, with K + the most important diffusing ion across the semipermeable membrane:…”
Section: Introductionmentioning
confidence: 99%
“…The second reason may be the mechanisms that produce the basal skin potential. These mechanisms are multiple and complex and include epidermal membranes, "skin battery" (voltage across the epidermis), sweat glands, and some diffusion and active-pumping mechanisms [13][14][21][22]33]. As a result, the return of wound potential to preinjury levels is a more prolonged and complex process that occurs slower than wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…Skin potential has typically been studied through transcutaneous potential measurement (the potential difference between the outer skin surface and the inner skin layers), which is an invasive method [14][15][21][22]]. An electrode must be inserted into the skin and another movable electrode placed on the skin.…”
Section: Introductionmentioning
confidence: 99%